Best Answer

Expression: -x^3 -x^2 -2x +1

Divided by: -x +1

Result: x^2 +2x +4 with a remainder of -3

Divided by: -x +1

Result: x^2 +2x +4 with a remainder of -3

More answers

The remainder is -1.

Q: What is the remainder when the expession of -x powered by 3 -x squared -2x plus 1 is divided by -x plus1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

It is a quadratic expession and when factored is: (x-6)(x+7).

6x3+29x2-40x-42 divided by 6x+5 Quotient: x2+4x-10 Remainder: 8

n is 2. To solve, do the division: . . . . . . . . .x2 +. 3x + (6-2n) . . . -------------------------- x-2 | x3 + x2 - 2nx + n2 . . . . .x3 -2x2 . . . . .-------- . . . . . . . .3x2 - 2nx . . . . . . . .3x2 - . 6x . . . . . . . .---------- . . . . . . . . . (6-2n)x + n2 . . . . . . . . . (6-2n)x - 2(6-2n) . . . . . . . . . ---------------------- . . . . . . . . . . . . . . . .n2 + 2(6-2n) But this remainder is known to be 8, so: n2 + 2(6-2n) = 8 ⇒ n2 - 4n + 4 = 0 ⇒ (n - 2)2 = 0 ⇒ n = 2

nine

None of the graphs that I can see!

Related questions

It is a quadratic expession and when factored is: (x-6)(x+7).

6x3+29x2-40x-42 divided by 6x+5 Quotient: x2+4x-10 Remainder: 8

The quotient works out as: x^2+2x+4 and there is a remainder of -3

Yes squared and powered are the same thing.

n is 2. To solve, do the division: . . . . . . . . .x2 +. 3x + (6-2n) . . . -------------------------- x-2 | x3 + x2 - 2nx + n2 . . . . .x3 -2x2 . . . . .-------- . . . . . . . .3x2 - 2nx . . . . . . . .3x2 - . 6x . . . . . . . .---------- . . . . . . . . . (6-2n)x + n2 . . . . . . . . . (6-2n)x - 2(6-2n) . . . . . . . . . ---------------------- . . . . . . . . . . . . . . . .n2 + 2(6-2n) But this remainder is known to be 8, so: n2 + 2(6-2n) = 8 ⇒ n2 - 4n + 4 = 0 ⇒ (n - 2)2 = 0 ⇒ n = 2

nine

2.1935

1

None of the graphs that I can see!

When any number is divided by itself, the quotient is always ' 1 ' exactly.

Imagine 4squared (16) divided by 4 (4). Therefore units squared divided by units would be units.

15t2 squared-t-15t+3=15t squared-14t+3